Carbon-containing Hydroxyapatite Obtained from Fish Bone as Low-cost Mesoporous Material for Methylene Blue Adsorption - Mukhamad Nurhadi; Ratna Kusumawardani; Wirhanuddin Wirhanuddin; Rahmat Gunawan; Hadi Nur (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
The carbon-containing hydroxyapatite has been synthesized using the fish bone obtained from East Kalimantan, Indonesia. The synthesis was conducted at varying calcination temperature (300-700 °C) and duration time (1-5 h). The carbon-containing hydroxyapatite were characterized by using Nitrogen adsorption-desorption, Fourier transform infrared spectroscopy, X-ray diffraction (XRD), Scanning electron microscopy (SEM), and Thermogravimetric analysis (TGA) and Differential thermal analysis (DTA). The carbon-containing hydroxyapatite nanoparticles consisted of the mesoporous structure with a specific surface area of 159 m2.g-1 and pore size of 44 Å. The carbon-containing hydroxyapatite nanoparticles were utilized as the adsorbent for the removal of methylene blue by varying the contact time, initial dye concentration, pH, adsorbent dosage and temperature. The maximum amount of adsorption capacity was 56.49 mg.g-1. The adsorption was well fitted with the Langmuir adsorption model (R2 ~ 0.998) and the pseudo-second-order model. This indicated that the dye molecules were adsorbed on the surface-active site of carbon-containing hydroxyapatite via chemical binding, forming an adsorbate monolayer. Hence, the adsorption capability corresponds to the physical properties such as the surface area and pore volume of hydroxyapatite because the larger surface area consists of higher binding sites for the adsorption. Thermodynamic parameters, including the Gibbs free energy (ΔG), enthalpy (ΔH), and entropy (ΔS), indicated that the adsorption of methylene blue onto the carbon-containing hydroxyapatite nanoparticles was spontaneous. Thus, carbon-containing hydroxyapatite nanoparticles can be applied as a low-cost adsorbent for the treatment of industrial effluents that are contaminated with the methylene blue.